Allogenic Mesenchymal Stem Cell Transplantation Ameliorates Nephritis in Lupus Mice via Inhibition of B-Cell Activation. Issue 12 (December 2013) - Ma, Xiaolei; Che, Nan; Gu, Zhifeng; Huang, Jing; Wang, Dandan; Liang, Jun; Hou, Yayi; Gilkeson, Gary; Lu, Liwei; Sun, Lingyun
Recent evidence indicates that bone marrow-derived mesenchymal stem cells (BM-MSCs) possess immunosuppressive properties both in vitro and in vivo. We have previously demonstrated that transplantation of human MSCs can significantly improve the autoimmune conditions in MRL/lpr mice. The current study aimed to determine the mechanisms by which murine BM-MSC transplantation (MSCT) ameliorates nephritis in MRL/lpr mice. In this study, we found that MSCT can significantly prolong the survival of MRL/lpr mice. Eight weeks after transplantation, MSCT-treated mice showed significantly smaller spleens than control animals, with fewer marginal zones (MZs), T1, T2, activated B-cells, and plasma cells. Moreover, serum levels of B-cell activating factor (BAFF) and IL-10 in MSCT-treated mice decreased significantly compared to those in the control group, while levels of serum TGF-β were increased. Notably, decreased BAFF expression in both spleen and kidney was accompanied by decreased production of anti-dsDNA autoantibodies and proteinuria in MSCT-treated mice. Since BAFF is mainly expressed by T-cells and dendritic cells, we incubated BM-MSCs and DCs together and found that the production of BAFF by DCs was suppressed by MSCs. Thus, our findings suggest that MSCT may suppress the excessive activation of B-cells via inhibition of BAFF production in MRL/lpr mice.